JOIN: an integrated platform for joint simulation of occupant-building interactions. (3rd July 2020) - Schaumann, Davide; Moon, Seonghyeon; Usman, Muhammad; Goldstein, Rhys; Breslav, Simon; Khan, Azam; Faloutsos, Petros; Kapadia, Mubbasir
Abstract : Several approaches exist for simulating building properties (e.g. temperature, noise) and human occupancy (e.g. movement, actions) in an isolated fashion, providing limited ability to represent how environmental features affect human behaviour and vice versa. To systematically model building-occupant interactions, several requirements must be met, including the modelling of (a) interdependent multi-domain phenomena ranging from temperature and sound changes to human movement, (b) high-level occupant planning and low-level steering behaviours, (c) environmental and occupancy phenomena that unfold at different time scales, and (d) multiple strategies to represent occupancy using established models. In this work, we propose an integrated platform that satisfies the aforementioned requirements thus enabling the joint simulation of building-occupant interactions. To this end, we combine the benefits of a model-independent, discrete-event, general-purpose framework with an established crowd simulator. Our platform provides insights on a building's performance while accounting for alternative design features and modelling strategies.